Women on the board and executive duration: Evidence for European listed firms - Achim Buchwald; Hanna Hottenrott (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
The participation of women in top-level corporate boards (or rather the lack of it) is subject to intense public debate. Several countries are considering legally binding quotas to increase the share of women on boards. Indeed, research on board diversity suggests positive effects of gender diverse boards on corporate governance and even firm performance. The mechanism through which these benefits materialize remain however mostly speculative. We study boards of directors in a large sample of listed companies in 15 European countries over the period 2003-2011 and find that female representation on firms' non-executive boards is associated with reduced turnover and an increase in tenure of executive board members. An increase in the performance-turnover sensitivity of executives suggests that this effect may be explained by better monitoring practices rather than by less effective control or a "taste for continuity".
Keywords: G34; J24; J63; L25; M00; 330; Corporate Governance; Executive Turnover; Gender; TMT Diversity